A role for the ventral visual stream in reporting movements. - Farrer, C; Passingham, R; Frith, C (2002)
In this experiment we contrast the neural activity associated with reporting a stimulus attribute with the activity that occurs when the same stimulus attribute is used to guide behavior. Reporting the characteristics of a stimulus differs from simply tracking that stimulus since reporting requires that a stimulus is explicitly recognized and associated with an arbitrary response. In one condition the subject used his right finger to follow a square that moved randomly on a screen. In a second condition he had to indicate changes in the direction of the square's movements by touching one of two report buttons with his right finger. Two other conditions were added to control for the differences in the form of movement between the two primary conditions. When the reporting condition was contrasted with the tracking condition (controlling for the differences in the form of movement), areas in the ventral visual system (the left ventral prefrontal cortex and the left inferior temporal cortex) were activated. This study shows that contrasting a manual task which involves a report with a manual task which does not activates the ventral visual system. However, the observation of additional activity in other areas suggests that, while activity in the ventral stream is necessary for reporting, it is not sufficient.